1997
DOI: 10.1177/027112149701700205
|View full text |Cite
|
Sign up to set email alerts
|

Toddlers Receiving Early Intervention in Childcare Centers

Abstract: This article presents a descriptive analysis of the early intervention services received by a group of 68 toddler-age children. The children were 30 months of age and early intervention services were delivered within childcare centers. Data were collected across family, child, and service characteristics. Results suggested that the children were receiving services distributed across special instruction, speech therapy, occupational therapy, and physical therapy delivered primarily at the childcare center. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Childcare classes are a potential solution to this shortage, and the accumulated research on early childhood inclusion has provided a foundation for using the childcare class as an inclusive placement option (Guralnick, 2001;Odom, 2000). Furthermore, examples of successful inclusive childcare programs do exist (W. H. Brown, Horn, Heiser, & Odom, 1996;Bruder & Staff, 1998;Bruder, Staff, & McMurrer, 1997;Jocelyn, Casiro, Beattie, Bow, & Kneisz, 1998;Quah, 1998). Childcare classes have other positive features that make these classes ideal intervention sites:…”
Section: Childcare Classroom As An Intervention Sitementioning
confidence: 99%
“…Childcare classes are a potential solution to this shortage, and the accumulated research on early childhood inclusion has provided a foundation for using the childcare class as an inclusive placement option (Guralnick, 2001;Odom, 2000). Furthermore, examples of successful inclusive childcare programs do exist (W. H. Brown, Horn, Heiser, & Odom, 1996;Bruder & Staff, 1998;Bruder, Staff, & McMurrer, 1997;Jocelyn, Casiro, Beattie, Bow, & Kneisz, 1998;Quah, 1998). Childcare classes have other positive features that make these classes ideal intervention sites:…”
Section: Childcare Classroom As An Intervention Sitementioning
confidence: 99%
“…Filla, Wolery, & Anthony, 1999;Strain, 1999;Warren, 1998). For example, studies have suggested that IFSPs still stress child outcomes to the exclusion of more broad-based family mediated outcomes and support strategies (Boone, McBride, Swann, Moore, & Drew, 1998;Bruder, Staff, & McMurrer-Kaminer, 1997;Farel, Shackelford, & Hurth, 1997;Summers et al, 1990); studies have also shown that service providers struggle with the delivery of services that include families (Filer & Mahoney, 1996;McBride & Peterson, 1997;McWilliam et al, 1995;McWilliam, Tocci, & Harbin, 1998). Additionally, both providers and researchers struggle with whether parent education and intervention on parent-infant interaction is encompassed within a family-centered framework (Mahoney et al, 1999;McCollum, 1999), whether early intervention should be child-centered or family-centered (Able- Boone, 1996, Beckman, Frank, & Newcomb, 1996, and whether the emphasis in early intervention should be relationship focused (Kelly & Barnard, 1999).…”
Section: Isaiahmentioning
confidence: 99%
“…Filla, Wolery, & Anthony, 1999;Strain, 1999;Warren, 1998). For example, studies have suggested that IFSPs still stress child outcomes to the exclusion of more broad-based family mediated outcomes and support strategies (Boone, McBride, Swann, Moore, & Drew, 1998;Bruder, Staff, & McMurrer-Kaminer, 1997;Farel, Shackelford, & Hurth, 1997;Summers et al, 1990); studies have also shown that service providers struggle with the delivery of services that include families (Filer & Mahoney, 1996;McBride & Peterson, 1997;McWilliam et al, 1995;McWilliam, Tocci, & Harbin, 1998). Additionally, both providers and researchers struggle with whether parent education and intervention on parent-infant interaction is encompassed within a family-centered framework (Mahoney et al, 1999;McCollum, 1999), whether early intervention should be child-centered or familycentered (Able- Boone, 1996, Beckman, Frank, & Newcomb, 1996, and whether the emphasis in early intervention should be relationship focused (Kelly & Barnard, 1999).…”
Section: Isaiahmentioning
confidence: 99%